Potensi Zat Aktif Ekstrak Tanaman dalam Formulasi Clay Mask - Adzkia, Muhammad Adit; Ratnasari, Devi; Shella, Tasya Permata; Cahyani, Theresia Natalie; Az-Zahra, Ailla; Valentin, Diva (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
in process